Motivasi Perspektif Al-Quran dalam Membangun Kepercayaan Diri : Kajian Surah At-Thaha 25-28: Tafsir Al-Misbah - Yoga Basyiril Sabirin; Hamidullah Mahmud (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
Self-confidence is an important element in achieving success and happiness, and has a significant positive relationship with motivation to learn. However, many individuals face challenges in building their self-confidence due to social pressure and negative experiences. In this context, this study explores sources of motivation from a Quranic perspective, specifically through Surah At-Thaha verses 25-28, which describe Prophet Moses' plea to Allah for peace and ease in facing life's challenges. Tafsir Al-Misbah by Quraish Shihab provides the insight that self-confidence should be built on faith in Allah and recognition of one's potential. This study also highlights the importance of social support, appreciation, and a supportive environment in building self-confidence. Using a qualitative approach and literature review, the results show that self-confidence can be strengthened through spiritual connection, internal reinforcement, and recognition of personal weaknesses, which ultimately encourages individuals to express themselves and reach their full potential. This research is expected to inspire readers to apply Quranic values in their daily lives, in order to increase self-confidence and freedom of expression.